Taat sebelum Hebat: Rahasia Kepemimpinan Kristen yang Bertumbuh dari Ketundukan (Jurnal Pendidikan Agama dan Teologi, 2025)
Contemporary Christian leadership encounters complex challenges when integrating intellectual, emotional, and spiritual intelligence. Limited understanding of obedience as a leadership foundation results in weakened spiritual development and integrity in ministry. This research employs a qualitative approach through comprehensive literature review, analyzing diverse theological literature, scientific journals, and academic sources discussing Christian leadership and obedience principles. The study reveals the concept of "Obedience Before Greatness" as a leadership paradigm positioning submission to God as a prerequisite for greatness, contrasting conventional leadership approaches that prioritize external achievements. Findings demonstrate that authentic and sustainable Christian leadership grows from obedience to God rather than personal ambition. Submission shapes character and integrity, producing leaders who serve with humility for God's glory.